2020
DOI: 10.3390/clockssleep2030021
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Dreams: An Online Survey

Abstract: Professional work is an integral part of modern life. According to the continuity hypothesis of dreaming, which states that dreams reflect waking life, work-related dreams should be quite common. As most dream content analytic studies are carried out in student samples, the topic of work in dreams is understudied. A few small studies indicate that the stress levels associated with the job are especially reflected in work-related dreams. Here, a total of 1695 people (960 women, 735 men) completed an online surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Spending more hours per week with work is directly related to the frequency of work‐related dreams (Schredl et al, 2020a; Schredl and Hofmann, 2003) thereby supporting the concept of a thematic continuity. Moreover, work‐related stress and emotions experienced towards work in waking life are strongly associated with the emotional tone of work‐related dreams, that is, work‐related dreams show both a thematic and emotional continuity (Schredl et al, 2009; Schredl et al, 2020a). In a diary study, Barnes et al (2021) were able to demonstrate that work‐related stress affects not only the emotional tone of dreams negatively but also the waking mood in the morning.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Spending more hours per week with work is directly related to the frequency of work‐related dreams (Schredl et al, 2020a; Schredl and Hofmann, 2003) thereby supporting the concept of a thematic continuity. Moreover, work‐related stress and emotions experienced towards work in waking life are strongly associated with the emotional tone of work‐related dreams, that is, work‐related dreams show both a thematic and emotional continuity (Schredl et al, 2009; Schredl et al, 2020a). In a diary study, Barnes et al (2021) were able to demonstrate that work‐related stress affects not only the emotional tone of dreams negatively but also the waking mood in the morning.…”
Section: Introductionmentioning
confidence: 96%
“…Work is an important part of waking life for most people all over the world (International Labour Office, 2019); thus work‐related dreams should occur quite frequently. Full‐time employees reported that up to 20% of their remembered dreams are work‐related (Schredl et al, 2020a; Schredl et al, 2005–2006; Schredl et al, 2010–2011). Even retired persons still dream quite often (15% to 20%) about their professional life (Schredl et al, 2020a; Achte et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even in the area of mobile phones, many individuals use clocks, e.g., in the sample ( N = 3084) of Montag et al [ 3 ], 45% of the participants regularly wore a wristwatch and 67% had an alarm clock for waking up in the morning. According to the continuity hypothesis of dreaming [ 4 , 5 ], we dream about topics that are important to us, e.g., family members [ 6 ], spouses [ 7 ], sexuality [ 8 ], our own children [ 9 ], pets [ 10 ] and work [ 11 ]. Given that punctuality and timekeeping is important (see above), the question arises as to how often clocks for measuring time occur in dreams.…”
Section: Introductionmentioning
confidence: 99%